Ankle Lateral Ligament Augmentation Versus the Modified Broström-Gould Procedure: A 5-Year Randomized Controlled Trial. Issue 3 (March 2019) - Porter, Mark; Shadbolt, Bruce; Ye, Xuan; Stuart, Robert
Background: "Ankle sprain" is a common injury, and >20% of patients may develop chronic instability for which surgery is indicated. The modified Broström-Gould (MBG) procedure remains the gold standard; however, there are a number of relative contraindications to this procedure, and the longer-term outcomes after the MBG have been questioned. An alternative procedure is augmentation of a primary repair with a ligament augmentation reconstruction system (LARS). Purpose: To conduct a randomized controlled trial testing the null-hypothesis that there is no difference in patient scored outcomes and activity levels, between patients undergoing a MBG procedure compared with those undergoing a primary repair with LARS augmentation, for lateral ligament instability of the ankle. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Patients who satisfied the inclusion criteria were invited to take part in the study. Patients were randomly allocated to undergo the LARS or MBG procedure. Both groups followed similar postoperative rehabilitation. Patients completed the Foot and Ankle Outcome Score (FAOS) before surgery and then at 1, 2, and 5 years after surgery. Tegner activity scores were recorded at 5years. The scores in the 2 groups were compared via statistical analysis ( P < .05). Results: Of the 50 patients satisfying the inclusion criteria, 47 agreed to take part in the study. Twenty-two were randomized to the LARS group and 25 to the MBG group. At 5 years, follow-up data were complete for 20 patients in the LARS group and 21 in the MBG. There were 2 failures in the MBG group and 0 in the LARS group. The LARS group had significantly better improvement in total FAOS at 1 year (mean ± SD, 92.4 ± 2.5 vs 78.2 ± 3.4, P = .005), 2 years (94.0 ± 3.0 vs 78.0 ± 5.2, P = .003), and 5 years (93.7 ± 6.0 vs 75.1 ± 5.5, P = .002) after surgery. The 5-year Tegner activity scores were higher in the LARS group (8.25 ± 1.1 vs 7.2 ± 0.9, P = .03). Conclusion: Among physically active patients with chronic lateral ligament instability, primary repair combined with LARS results in better total FAOS at 5-year follow-up and higher Tegner activity scores as compared with the MBG procedure. Registration: ACTRN12618000906257 (Australia New Zealand Clinical Trial Registry).